Analisis Alur Pergerakan Baggage Towing Tractor di Area Make Up dan Breakdown Bandar Udara Internasional Kualanamu Deli Serdang - Hidayat, Ari Hidayat; Wahyudono; Feri Adriansyah (Jurnal Ground Handling, 2025)
This study aims to examine the implementation of Standard Operating Procedures, the availability of markings and signs, and the influence of supervision in the operation of Baggage Towing Tractors (BTT) in the Make Up and Breakdown areas of Kualanamu International Airport in Deli Serdang. This study employs a qualitative descriptive approach involving observation and interviews, supported by quantitative data analysis from a questionnaire distributed to 50 respondents. Data analysis was conducted using validity, reliability, normality, linearity, and multiple linear regression tests to assess the impact of supervision and vehicle activity during peak hours on the smooth operation of BTT. The results of the study reveal that effective supervision and operator discipline play a significant role in facilitating the flow of BTT vehicles. Additionally, the lack of clear markings and signs causes irregularities in movement on the ground. Based on these findings, this study recommends enhancing supervision, enforcing SOPs, and installing markings and signs in accordance with applicable safety standards. The implementation of these measures is expected to improve the efficiency of baggage loading and unloading processes as well as operational safety at Kualanamu International Airport, Deli Serdang.